Pengaruh Employer Branding dan Media Sosial Perusahaan terhadap Minat Kerja Generasi Z di Singaparna - Astri Wulandari; Sri Sudiarti (CV. ALIM'SPUBLISHING, 2026)
Increasingly intense market competition in the digital era requires companies to implement effective recruitment strategies to attract the best talent, particularly from Generation Z. This generation is highly familiar with digital technology and social media, making digital platforms their primary source of information regarding employment opportunities. In this context, employer branding and corporate social media utilization play important roles in shaping perceptions and influencing job application intentions. Although previous studies have examined the influence of employer branding and social media on recruitment outcomes, the findings remain inconsistent and often contradictory. Therefore, this study aims to analyze and evaluate the effects of employer branding and the intensity of corporate social media usage on the job application intentions of Generation Z. The research focuses on Generation Z individuals residing in the Singaparna area. This study is expected to provide a more comprehensive understanding of the factors influencing job application decisions among young people in the digital era. The findings are anticipated to serve as valuable insights for companies in designing more effective, innovative, and targeted recruitment strategies that align with the characteristics and preferences of Generation Z as the future workforce.